TINGKAT KEMAMPUAN BERPIKIR SISWA DENGAN PENDEKATAN METAKOGNITIF DISKURSIF DAN PENDEKATAN KONVENSIONAL - Lubur, Dorothea Novia L.; Ate, Dekriati (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2018)
[Title: The Level of Thinking Ability of Students with Metacognitive-Discursive Approaches and Conventional Approaches]. This paper discusses the different levels of thinking ability of students in the classroom using metacognitive-discursive and conventional approaches in SMPK St. Aloysius Weetebula. PISA is one of the tests that measure the level of critical thinking skills. The low PISA results of Indonesian students are caused by the weak ability to solve high-level problem problems, the evaluation system in Indonesia that still uses low-level questions, and students are accustomed to obtaining and using formal mathematical knowledge in class. One way to overcome this problem is STKIP Weetebula in collaboration with German misereor to improve the quality of education on the island of Sumba. To achieve this goal, an entrance test was conducted for all 7th-grade students of Aloysius Middle School in 2014 and 2017. In some exercises, there were very high score differences. From this exercise, one of the problems with the highest difference is a fraction. This research is an interpretative study through the analysis of student answers based on theory and descriptive analysis to measure differences in scores obtained by two groups of students. Research results in class with metacognitive-discursive approach 17 (89.47%) answered correctly and 2 (10.53%) of 19 students answered incorrectly, while in class with conventional approach 3 (2.59%) of 116 students answered correctly and 113 (97.41%) of 116 students answered incorrectly. Based on the results of this study concluded that students in the classroom with a metacognitive-discursive approach to learning more than students in other.